Nigella sativa oil and thymoquinone reduce oxidative stress in the brain tissue of rats exposed to total head irradiation. (1st February 2020) - Demir, Elif; Taysi, Seyithan; Ulusal, Hasan; Kaplan, Davut Sinan; Cinar, Kadir; Tarakcioglu, Mehmet
Abstract: Purpose: To evaluate the antioxidant and radio-protective effects of Nigella sativa oil (NSO) and thymoquinone (TQ) on radiation-induced oxidative stress in brain tissue. Materials and methods: Fifty-four Sprague-Dawley rats were divided into six groups to test the radio-protective effectiveness of Nigella sativa oil and thymoquine administered by either orogastric tube or intraperitoneal injection. Appropriate control groups were also studied. Results: Brain antioxidant capacity, as measured by the levels of total superoxide scavenger activity (TSSA), non-enzymatic superoxide scavenger activity (NSSA), superoxide dismutase, paraoxonase (PON) activities, total antioxidant status and total sulfhydryl (-SH) group, were lower in the irradiation (IR) only group while xanthine oxidase (XO) activity, total oxidant status (TOS), oxidative stress index (OSI) and lipid hydroperoxide (LOOH) levels were higher in the group compared with all other groups. Brain glutathione-S-transferase (GST) activity significantly decreased in the IR only group when compared with the control groups. Glutathione peroxidase (GSH-Px) activity was lower in the IR only, NSO plus IR, TQ plus IR groups when compared with the control group of TQ. Arylesterase (ARYL) activity was not statistically significant in the IR only group compared with all other groups. Conclusions: The results suggest that Nigella sativa oil (NSO) and its active component, TQ, clearly protect brain tissue from radiation-induced oxidative stress.